Capability for infrastructure asset capacity management - G. Too, Eric (International Journal of Strategic Property Management, 2011)
Infrastructure capacity management is the process of ensuring optimal provision of infrastructure assets to support business operations. Effectiveness in this process will enable infrastructure asset owners and its stakeholders to receive full value on their investment. Management research has shown that an organisation can only achieve business value when it has the right capabilities. This paradigm can also be applied to infrastructure capacity management. With competing needs for limited organisation resources, the challenge for infrastructure organisations is to identify and invest their limited resources to develop the right capabilities in the management of their infrastructure capacity. Using a multiple case study approach, the challenges faced in the management of infrastructure asset capacity and the approaches that can be adopted to overcome these challenges were explored. Conceptualising the approaches adopted by the case participants, the findings suggest that infrastructure organisations must strengthen their stakeholder connectivity capability in order to effectively manage the capacity of their infrastructure assets.First Publish Online: 4 Jul 2011